Morphometric variability of narrow-leaved ash samaras at the test-tree level - Čortan Dijana; Mačar Vedrana; Vukičević Vladimir; Šijačić-Nikolić Mirjana (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2017)
The aim of this research is to assess F. angustifolia test tree variability based on the morphometric traits and shape of samara from the locality Karapandža. Twenty adult trees were randomly selected. From each individual 100 fully developed samaras were analyzed. The following traits were analyzed: the length and width of samara, the length of seed, ratio between the length of seed and samara, the weight of 100 seeds by individual, samara shape and samara top shape. The obtained results indicated a considerable variability within the studied individuals at the level of samara morphometric traits. Considering that all sampled individuals were from the same populations we could suppose that this variability was not induced by different environmental factors (climate or soil), then with the existence of specific genotypes. Classification based on samara size says that our individuals could belong to large size samaras, i.e. the type known as f. macrocarpa. However, since there is no uniformity of samara shapes within the majority of studied individuals we cannot classify them in accordance with samara shape classification.